Edwards-Bell-Ohlson valuation model : an evaluation of Singapore stocks 1995-1999. - Chua, Teck Wee. (2008)
In this study, the EBO is tested in the Singapore stock market from 1995-1999 to evaluate its ability in estimating intrinsic value as well as its predictive power in forecasting stock returns.